2014
DOI: 10.6007/ijarbss/v4-i6/969
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Board Characteristics and the Sustainable Development of Companies Listed at Tehran Stock Exchange

Abstract: The main objective of this paper is to investigate the relationship between board characteristics and the sustainable growth of companies listed at Tehran Stock Exchange. Board characteristics in this study include the size of the board, number of board meetings, the share of non-bound managers of the board, duality of managing director duties and maintaining shares of the Board of Directors. According to previous similar studies, firm size and financial leverage are considered as control variables. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Prior studies investigated the impact of corporate governance mechanisms on factors that may have considerable effect on the corporate sustainable growth and reached mixed results. On one side, and based on a sample of 54 companies listed on Tehran Stock Exchange during the period 2006-2012, Zare et al (2014) didn't find any significant relationship between board size, meetings, shareholdings, share of independent directors on board and sustainable growth. But they found that managing director duality of duties is negatively and significantly related to growth rate.…”
Section: Corporate Sustainable Growthmentioning
confidence: 92%
See 1 more Smart Citation
“…Prior studies investigated the impact of corporate governance mechanisms on factors that may have considerable effect on the corporate sustainable growth and reached mixed results. On one side, and based on a sample of 54 companies listed on Tehran Stock Exchange during the period 2006-2012, Zare et al (2014) didn't find any significant relationship between board size, meetings, shareholdings, share of independent directors on board and sustainable growth. But they found that managing director duality of duties is negatively and significantly related to growth rate.…”
Section: Corporate Sustainable Growthmentioning
confidence: 92%
“…This paper contributes to the literature of corporate governance and its impact on corporate sustainable growth. Although several research papers have been conducted to examine the impact of corporate governance characteristics in general, and board of directors' characteristics in particular, on corporate sustainable growth (Maher, & Andersson, 2000;Zare, Moeinadin, & Heyrani, 2014;Li, Liu, & Ren, 2015;Mukherjee & Sen, 2019), however up to my knowledge, no prior research examined the association between AC characteristics and corporate sustainable growth. Also, this paper will help policymakers and regulators to understand how AC effectiveness is associated with the sustainable growth of non-financial firms listed on EGX.…”
Section: Introductionmentioning
confidence: 99%
“…Tujuan manajemen persediaan adalah untuk mencapai keseimbangan yang tepat antara kebutuhan produksi dan biaya persediaan yang efisien [9]. Akan tetapi jika persediaan bahan baku terlalu besar dapat mengakibatkan tingginya biaya untuk menyimpan dan memelihara bahan baku tersebut, disamping itu jika ditinjau dari segi finansial yaitu hal yang tidak efektif karena terlalu besarnya barang modal yang menganggur dan tidak berputar [10].…”
Section: Penulis Pertama Dkkunclassified